The Social Image of Women in the Novel Dear Allah by Diana Febi - Nur Faojiyah; Robert Rizki Yono; Nurchalistiani Budiana (CV. Rayyan Dwi Bharata, 2024)
The aim of this research is to describe the social image of women in the novel Dear Allah by Diana Febi. The research method used in this research is descriptive qualitative using a feminist approach. The data obtained is in the form of words, sentences and quotes in the novel Dear Allah by Diana Febi. The data collection technique uses note-reading techniques. The data analysis technique in this research uses descriptive analysis. The results of research on the social image of women in the novel Dear Allah by Diana Febi are that there is a social image of women in the family aspect and a social image of women in the community aspect. In the novel Dear Allah, the social image of women in the family aspect is depicted through the character Naira, who is portrayed as a wife who fulfills her responsibility to serve her husband, fulfills her obligations, is painstaking, understanding, obedient, and as a child who is filial to her parents. The social image of women in the societal aspect is that of women who care about their surroundings, because women are social creatures who need other people.